Financial Metrics and Property Stock Returns: Evidence from Indonesia: Dampak Metrik Keuangan terhadap Tingkat Pengembalian Saham Properti: Bukti dari Bursa Efek Indonesia - Mochammad Efendi; Sriyono Sriyono (Academia Open, 2023)
This quantitative study examines the influence of Market Value Added, Economic Value Added, Earnings Per Share, and Operating Cash Flow on property stock returns in the Indonesian stock exchange. The research focuses on a sample of 27 property companies for the period 2017-2020, selected from a population of 54 companies. Multiple regression analysis using Eviews version 9 is employed as the analytical method. The findings indicate that Market Value Added, Economic Value Added, and Earnings Per Share do not significantly affect stock returns. However, Operating Cash Flow demonstrates a significant impact on stock returns. Additionally, when considered together, Market Value Added, Economic Value Added, Earnings Per Share, and Operating Cash Flow collectively exhibit a significant influence on property stock returns. This study provides valuable insights for investors, analysts, and policymakers in understanding the determinants of stock returns in the property sector, offering implications for decision-making and investment strategies in the Indonesian stock market. Highlights: Financial metrics: Investigating the impact of Market Value Added, Economic Value Added, Earnings Per Share, and Operating Cash Flow on property stock returns. Stock return determinants: Analyzing the significance of these financial metrics in influencing the returns of property stocks. Market implications: Providing insights for investors and policymakers regarding the role of financial metrics in predicting and understanding property stock returns. Keywords: Market Value Added, Economic Value Added, Earnings Per Share, Operating Cash Flow, property stock returns